(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The purpose of the study is to analyze the impact of IoT on the development of smart cities and urban infrastructure, as well as to develop proposals for the effective use of these technologies. It has been established that the greatest effect from the implementation of IoT is achieved in the areas of transport logistics, environmental monitoring, energy management, and public safety, which confirms the feasibility of using sensor networks for operational data collection. An important direction is the combination of IoT with artificial intelligence systems for predictive analysis of transport flows, the state of engineering networks and environmental indicators. It was determined that the implementation of IoT contributes to increasing the efficiency of resource use, reducing operating costs, improving the quality of city services and creating the prerequisites for the digital transformation of municipal management. The practical significance of the results obtained lies in the possibility of applying the proposed approaches in the development of digital development programs for cities, as well as in the creation of comprehensive platforms for monitoring urban infrastructure taking into account the requirements for cybersecurity, equipment compatibility and personal data protection.